Spirituality and leadership effectiveness among Muslim leaders in public sector / Mohd Zakey Ramlee - Ramlee, Mohd Zakey (2017)
Currently, Islamic concept has become more prominent in the development of society. It is no longer unfamiliar among the world community. In addition, the administration and management based on Islamic concept is also becoming increasingly popular among organizations around the world. Since many scholars believe that there is still lack of study regarding Islamic perspective in management, thus the purpose of this research is to examine about this problem and explore more about Qur’an way of leadership. On the other hand, the study also explores the relationship between Islamic spirituality concept and the effectiveness of the leadership. The independent variables involved in this research are belief (iman), rituals (ibadat) and repentance (tawbah) while the dependent variable is leadership effectiveness. A total of 180 respondents among civil servants in public sector within Kuching and Kota Samarahan were participated in the survey. Those respondents were from federal government, state government, local government and public university. The result belief was found to be significant with very strong correlation and positive relationship with leadership effectiveness. As for repentance, the result also shows that this variable was significant with a strong correlation and positive relationship with leadership effectiveness. Meanwhile for rituals, the result shows that this variable has insignificant with a moderate correlation and positive relationship with leadership effectiveness. The main contribution of this research is that it has extending the leadership effectiveness study based on Islamic view and it focusing more on the Malaysian public sector specifically within Kuching and Kota Samarahan. In addition, the findings may give potential inputs and an insight to organization’s leader to adopt those spirituality values in their daily life in order to develop the leadership skills and improve the effectiveness. Apart from that, it reveals what is the factor that influencing the most on the leadership effectiveness among leaders in public sector. Suggestions for future research were also provided in this research.